2003
DOI: 10.1161/01.res.0000078346.60663.a0
|View full text |Cite
|
Sign up to set email alerts
|

What Sets the Long-Term Level of Renal Sympathetic Nerve Activity

Abstract: Abstract-Increasing evidence suggests elevated sympathetic outflow may be important in the genesis of hypertension. It is thought that peripheral angiotensin II, in addition to its pressor actions, may act centrally to increase sympathetic nerve activity (SNA). Without direct long-term recordings of SNA, testing the involvement of neural mechanisms in angiotensin II-induced increases in arterial pressure is difficult. Using a novel telemetry-based implantable amplifier, we made continuous recordings of renal S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
133
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 43 publications
10
133
1
Order By: Relevance
“…The decrease in plasma renin concentration that we observed with baroreceptor stimulation is promising given the important contribution of the renin-angiotensin system in sodium balance and long-term blood pressure control. 28,34,37 Heterogeneity in the contribution of baroreflex and sympathetic nervous system mechanisms to blood pressure may have contributed to variability in the response to carotid sinus stimulation in our subjects. Anatomic and functional properties of the carotid sinus, as well as the implantation procedure, may also play a role.…”
Section: Discussionmentioning
confidence: 98%
“…The decrease in plasma renin concentration that we observed with baroreceptor stimulation is promising given the important contribution of the renin-angiotensin system in sodium balance and long-term blood pressure control. 28,34,37 Heterogeneity in the contribution of baroreflex and sympathetic nervous system mechanisms to blood pressure may have contributed to variability in the response to carotid sinus stimulation in our subjects. Anatomic and functional properties of the carotid sinus, as well as the implantation procedure, may also play a role.…”
Section: Discussionmentioning
confidence: 98%
“…Bell et al could find no change in directly recorded basal RSNA 3 to 5 weeks after renal wrapping in rabbits, 16 and there is evidence of decreased RSNA in dogs 17 and rabbits with Ang-induced hypertension. 8 Thus there is general agreement that RSNA is not elevated in this form of hypertension.…”
Section: Head and Burke Sympathetic Responses In Hypertensive Rabbitsmentioning
confidence: 97%
“…Barrett et al first reported successful recording of renal sympathetic nerve activity in conscious rabbits continuously for more than 7 days. 15 Tan et al implanted Data Sciences International (DSI, St. Paul, MN, USA) transmitter to directly record left stellate ganglion nerve activity, left vagal nerve activity and left atrium local bipolar electrograms or surface electrocardiography simultaneously in ambulatory dogs over several weeks. 16 Intermittent rapid atrial pacing was performed and ANS activity was monitored when the pacemaker was turned off.…”
Section: Sympathetic-parasympathetic Interaction In Afmentioning
confidence: 99%